Analysis Of Factors Causing Diarrhea In Children Aged 1 – 3 Years In The Working Area Of Simpang Tiga Riau Puskesmas Year 2021 - Roy Wilson Sihaloho (Sean Institute, 2021)
Diarrhea is a disease characterized by an increase in the frequency of defecation more than usual (> 3 times/day) accompanied by a change in the consistency of the stool to become liquid with or without blood and/or mucus. In Indonesia, the number of sufferers of diarrhea is around 60 million events each year, most of the 70% - 80% of these sufferers are under the age of 3 years, more or less than 40 million events. The increase in the number of sufferers of diarrhea is associated with factors that influence the occurrence of diarrhea such as environmental health factors, hand washing factors and food sanitation factors. This type of research is a cross-sectional analysis design with the aim of analyzing the factors that cause diarrhea in children aged 1-3 years in the Simpang Tiga Riau Health Center work area in 2021. The population of this study is all mothers who have children aged 1-3 years who suffering from diarrhea who came for treatment at the Simpang Tiga Riau Health Center in August 2020 - February 2021. The sample in this study were 70 people and the sampling method used the Accidental Sampling method. This type of research data is primary data by distributing questionnaires to respondents. The data obtained was analyzed by looking at the total percentage of data collected and presented in frequency distribution tables. The results of the study stated that around 70% of the response by washing hands was at risk of having a child experience diarrhea, there was a relationship between hand washing (p=0.000), food sanitation (p=0.003) and the incidence of diarrhea in children aged 1-3 years. For this reason, it is recommended for mothers who have children aged 1-3 years to pay more attention to environmental health, teach their children good hand washing and pay attention to food sanitation to prevent diarrhea in these children. For officers at the Simpang Tiga Riau Health Center, especially nurses in the infectious disease handling section, to provide counseling to mothers who have children aged 1-3 years about the factors that cause diarrhea in children and provide an explanation of how to prevent diarrhea.